Multivariate analysis of abundance and distribution of fish species in coast of Ghana, West Africa - Amponsah, Samuel KK; Ameyaw, Anita; Asare, Cephas (Research in Agriculture Livestock and Fisheries, 2022)
Marine fishes are currently experiencing population decline which has severe repercussions on food security, especially in fishing households. However, without assessing the distribution and abundance of these marine fishes, ensuring sustainable management will become impossible. Therefore, the study aimed at applying multivariate techniques to determine the biodiversity of fishes along the coast of Ahanta West, Ghana. Fish samples were collected daily through experimental fishing from November-December, 2011. Data obtained from the study were analyzed for ecological indices, species diversity, and community structure using PAST and PRIMER v6 software. From the results, Pteroscion peli (19.2%), Galeoides decadactylus (11.7%), and Brachydeuterus auritus (9.0%) were the dominant fishes. Multivariate analysis identified three main assemblages of fishes, at 18%. For the ecological indices, the species dominance index (SDI) ranged from 0.89 to 0.93, which indicated that the fish species were highly dominated by a few species. The Shannon Weiner index (SWI) and Species Richness index (SRI) spanned between 2.64 – 2.92 and 4.43 – 648 respectively, showing high diversity of fish species. It is concluded that the marine environment along the Ahanta West, Ghana is rich in fish species diversity, and hence, there is the need to regulate existing fishing operations for sustainable utilization and conservation of these commercially important fish species. Res. Agric., Livest. Fish.9(1): 57-59, April 2022